Knowledge, attitude, and practice of pre-diabetic older people regarding pre-diabetes - Vahid Pakpour; Fatemeh Molayi; Hossein Nemati (BMC Geriatrics, 2024)
Abstract Background One of the risk factors of diabetes is the pre-diabetes stage which is significantly prevalent in older people. Knowledge, attitude, and practice of the pre-diabetic stage are of great importance and can decrease complications. The present study aimed to determine the knowledge, attitude, and practice of the pre-diabetic older people. Methods : This cross-sectional study was conducted from April 2022 to August 2022 on 219 pre-diabetic older people referring to Sina Hospital in Tabriz, one of the most populated cities in the northwest of Iran. Data were collected using questionnaires of Knowledge, Attitude, Practice-Prediabetes Assessment Questionnaire (KAP-PAQ). The data were analyzed by SPSS 21. Results The mean scores of knowledge (in the range of 0–17), attitude (in the range of -10, + 10), and practice (in the range of 0–26) were 1.72 ± 1.0, 2.24 ± 1.92, and 5.76 ± 2.61, respectively. The older people’s knowledge and practice levels in the pre-diabetes stage were low and about 50% of them had negative views. According to the Spearman correlation test, there was a positive significant relationship between the older people’s knowledge and practice (p < 0.001, r = 0.234). Conclusions The older people in the pre-diabetes stage had low knowledge and attitude and a negative viewpoint towards correcting lifestyle on diet, exercising and physical activity, weight control, diagnostic and screening methods. Increased knowledge about pre-diabetes and strengthened positive attitude towards correcting lifestyle through counseling as well as empowering the pre-diabetic older people can increase the efficiency of pre-diabetes prevention and control programs and prevent its progression to the diabetes stage.